Аргументированная детализация новой концепции о переходных процессах в электрических цепях - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The appearance of a section with slowly increasing current in the transient process of an RL circuit is substantiated. The expansion of jump-like input voltages in a series is proposed. The problem concerning the transient processes in electrocircuits is solved on the basis of the new conception.